Penerapan Teknik Cognitive Restructuring Dalam Meningkatkan Self Regulation (Studi Kasus Klien “A” Simpang Polda Palembang) - Muhammad Miftahul Ilmi Ilmi; Suryati suryati; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This research is entitled "Application of Cognitive Restructuring Techniques in Increasing Self Regulation (Case Study of Client "A" Palembang Police Intersection). This research is very useful for client "A" who is a prostitute who has low self-regulation. Because of that, counseling is needed with the application of cognitive restructuring techniques in increasing self-regulation, so that clients can lead a good life, able to manage their emotions, behavior and thoughts. This type of research is field research (flied research) with descriptive qualitative research. The subject of the study was a prostitute who was located at the Palembang Police intersection. In this study data collection techniques through observation, interviews, documentation. And using the data analysis model of Robert K.Yin, namely Pattern Matching, Explanation, and Time Series Analysis. This study applies the Cognitive Restructuring technique in increasing Self Regulation, by going through seven stages namely, Rationale, Identifying negative thoughts of clients, recognition and practice of positive thoughts, shifting thoughts, introduction and practice of self-declaration, homework, and evaluation. From providing counseling by applying cognitive restructuring techniques, clients are able to increase their self-regulation.